Beauty and the beast - DeMornay, Rebecca, 1963-; Graber, Yossi; Savage, John, 1949-; Satrina, Carole Lucia; Golan, Menahem, 1929-; Globus, Yoram; Marner, Eugene; Villeneuve, Gabrielle-Suzanne Barbot Gallon, dame de, ca. 1695-1755.; MGM Home Entertainment Inc. (Santa Monica, CA : MGM Home Entertainment, 2005)
Trading her freedom to save her beloved father, young Beauty enters into a lonely life at the magic-filled castle of the frightful-looking Beast. But as the unhappy Beast gradually reveals the secret of his heart to her, Beauty sees beyond his physical form and her love works a miraculous change.
DVD; Dolby digital stereo. surround; region 1, full screen format.
Soundtrack in English; subtitles in English, French or Spanish; closed-captioned.
Rebecca De Mornay, Yossi Graber, John Savage.
Director of photography, Avi Karpick ; editor, Tova Ascher ; music, Lori McKelvey.
Based on the fairy tale by Madame de Villeneuve.
Originally produced as a motion picture in 1986.
Keywords: Fathers and daughters -- Drama; Castles -- Drama; Magic -- Drama; Feature films; Musical films; Film adaptations; Fantasy films; Video recordings for the hearing impaired; Musical -- Feature; Fantasy -- Feature; Musical films; Fantasy films